BIMBINGAN BELAJAR EAGLE NEST MELALUI PEMBELAJARAN DARING DALAM MASA PANDEMI - Wiyun Philipus Tangkin; Wiputra Cendana (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2021)
Eagle Nest tutoring is a movement that cares about the importance of education for all circles, which started from 2017 until now. This tutoring service serves children who live in the Griya Karawaci area with middle to lower economic level (marginal people). Based on these needs, UPH-Teachers College held Tutoring at Perum Griya Karawaci, Curug-Tangerang. This Tutoring aims to provide debriefing in the form of additional learning and mentoring for children to learn from the kindergarten, elementary, junior high, and high school levels. The material taught is adjusted to the school material of each student. The method of learning to play will be applied to 3rd grade kindergarten-elementary school students while for 4th grade elementary school students onwards it will be adjusted to the material being taught. This Tutoring activity is held 2 times per week in the form of online learning, and those who teach are students from the Faculty of Education - Teachers College who have been previously selected. The results of the evaluation after running from the beginning to the middle of 2021 are that this activity helps students improve reading, writing, and arithmetic skills for kindergarten-elementary school students and improve math skills for junior-high school students. This activity can improve the ability of children in holistic tutoring, not only academically, but also in character. In addition, students who serve as tutors can also use this activity as a medium to practice teaching skills and their calling as adult teachers.